Effect of Net Profit Margin, Sales Growth, Profitability on Dividens Pay-Out Ratio with Managerial Ownership as Moderation - Naibaho, Eduard Ary Binsar; Widyastari, Nurul (Jurnal Keuangan dan Perbankan, 2023)
This study aims to test and analyze the relationship between net profit margin, sales growth,profitabilitytodividendpay-outratiowithmanagerialownershipasamoderating. The source of this study data usessecondarydata fromcompanies availableat SPCapitalIQwithatotalof260 observationsthathavemetthecriteriausedusingpurposivesamplingtechniques. This research shows that net profit margin and profitability have a positive influence on the dividend pay-out ratio. Sales growth has a negative influence on the dividend pay-out ratio. The study also showed that managerial ownership as a moderating variable strengthens the relationship between net profit margin, sales growth and profitability to dividend pay-out ratio.